Habilidades metalingüísticas y decodificación lectora en alumnos del primer grado de primaria de una institución educativa del Callao - Dávila Paz, Mónica Cecilia (2012)
This correlational descriptive research intended to show the relationship between has order to demonstrate the relationship between metalinguistic skills and decoded reading levels in first grade primary students of a private school in Callao. The sample consisted of 31 students chosen intentionally not random. Two instruments were applied: The test of metalinguistic skills (THM) elaborated by Gomez, Valero, Buadas and Perez and adapted by Panca (2000) which assesses syllabic awareness, intrasyllabic awareness and phonemic awareness and the screening test for dyslexia developed by Mabel Condemarín, supplemented with standards developed by Berdicewski, Millicic and Orellana which evaluates the first, second and third reading level. The results show that there is a considerable positive relation (r = 0.627 ( p < 0.01) between levels of phonological awareness and the levels of reading decoding. Likewisse, There is a weak positive relation (r = 0.374) between syllable level and reading decoding ( r = 0.698 between the phonetic level and reading decoding.